Survival after radical prostatectomy versus radiation therapy in clinical node-positive prostate cancer - Chierigo, Francesco; Borghesi, Marco; Würnschimmel, Christoph; Flammia, Rocco S; Horlemann, Benedikt; Sorce, Gabriele; Hoeh, Benedikt; Tian, Zhe; Saad, Fred; Graefen, Markus; Gallucci, Michele; Briganti, Alberto; et al. (The Prostate, 2022)
AIM: To compare overall mortality (OM), cancer-specific mortality (CSM), and other cause mortality (OCM) rates between radical prostatectomy (RP) versus radiotherapy (RT) in clinical node-positive (cN1) prostate cancer (PCa). MATERIALS AND METHODS: Within Surveillance, Epidemiology, End Results (SEER) (2004-2016), we identified 4685 cN1 PCa patients, of whom 3589 (76.6%) versus 1096 (24.4%) were treated with RP versus RT. After 1:1 propensity score matching (PSM), Kaplan-Meier plots and Cox regression models tested the effect of RP versus RT on OM, while cumulative incidence plots and competing-risks regression (CRR) models addressed CSM and OCM between RP and RT patients. All analyses were repeated after the inverse probability of treatment weighting (IPTW). For CSM and OCM analyses, the propensity score was used as a covariate in the regression model. RESULTS: Overall, RT patients were older, harbored higher prostate-specific antigen values, higher clinical T and higher Gleason grade groups. PSM resulted in two equally sized groups of 894 RP versus 894 RT patients. After PSM, 5-year OM, CSM, and OCM rates were, respectively, 15.4% versus 25%, 9.3% versus 17%, and 6.1% versus 8% for RP versus RT (all p < 0.001) and yielded respective multivariate hazard ratios (HRs) of 0.63 (0.52-0.78, p < 0.001), 0.66 (0.52-0.86, p < 0.001), 0.71 (0.5-1.0, p = 0.05), all favoring RP. After IPTW, Cox regression models yielded HR of 0.55 (95% confidence interval [CI] = 0.46-0.66) for OM, and CRR yielded HRs of 0.49 (0.34-0.70) and 0.54 (0.36-0.79) for, respectively, CSM and OCM, all favoring RP (all p < 0.001). CONCLUSIONS: RP may hold a CSM advantage over RT in cN1 PCa patients.
Keywords: SEER Program; Risk Factors; nádory prostaty; prostatektomie; Humans; lidé; program SEER; Prostatic Neoplasms; Prostatectomy; Male; mužské pohlaví; výsledek terapie; rizikové faktory; Treatment Outcome